Evaluation of zinc rich paint (ZRP) efficiency on mild steel in seashore environment - Azizul Helmi, Sofian; Noda, Kazuhiko (ECS, 2012)
Exposure to humidity and salinity in the atmosphere will accelerate the corrosion process of steel. Corrosion of metallic surfaces can be reduced or controlled by the addition of chemical compounds to corrode. Zinc is one of the most important components for commercial application in the corrosion protection of steel, for which it is extensively employed to coat or galvanize ferrous metallic products. In this paper is focused with directly on efficiency of ZRP coating applied on steel substrate under NaCl solution as artificial seashore environment by using Open Circuit Potential (OCP) measurements and Electrochemical Impedance Spectroscopy (EIS).